"Before I die I want to …": An experience of death education among university students of social service and psychology. Issue 2 (November 2018) - Testoni, Ines; Iacona, Erika; Fusina, Sonia; Floriani, Maddalena; Crippa, Matteo; Maccarini, Andrea; Zamperini, Adriano
The censorship of death and dying has removed the "memento mori" practices, and in order to reintroduce this practice, some "Before I die" projects have been increasingly implemented. Running in parallel, in the syllabi of social service and psychology students, some experiences of death education has commenced. This study illustrates the results of a qualitative research conducted on the "Before I die I want to …" Polaroid ® Project (BIDIWT), which is divided into two phases. The first phase entails an analysis of the wishes collected from the United States, Japan, India, and Italy. The second phase refers to the analysis of the captions of the BIDIWT realized from two groups of undergraduates, with regard to the effect of such experience on their religiosity, representation of death, and fear of death.